A Juridical Analysis of Unregistered Marriage Agreements at the Marriage Registration Office - Chairul Yunadi; Teuku Saiful; Iman Jauhari (International Journal of Law, Crime and Justice, 2026)
Marriage agreements are agreements entered into before or after marriage that generally regulate the separation of marital assets. Under Article 147 of the Indonesian Civil Code and Article 29 of the Marriage Law, such agreements must be executed in the form of a notarial deed and registered with the Marriage Registration Office to be legally binding upon third parties. In practice, however, many spouses fail to register their marriage agreements, creating potential legal uncertainty. This study aims to analyze the legal consequences of unregistered marriage agreements and examine the responsibility of notaries in preventing such situations. The research employs a normative juridical method using statutory, case, and conceptual approaches. Primary, secondary, and tertiary legal materials were analyzed qualitatively. The findings reveal that an unregistered marriage agreement remains valid and binding only between the spouses but has no legal effect on third parties, as stipulated in Article 152 of the Indonesian Civil Code. Notaries are responsible not only for drafting marriage agreement deeds but also for providing legal counseling to ensure their registration with the Civil Registration Office or the Office of Religious Affairs. Therefore, spouses should register their marriage agreements to ensure legal certainty and protection for all parties.